Macrolide resistance in Mycoplasma pneumoniae in adult patients - Xie, Panpan; Zhang, Yue; Qin, Yanhong; Fang, Yun; Yang, Ning; Bai, Yunbiao; Zhi, Shimeng; Niu, Wenkai; Wang, Fusheng; Yuan, Xin (Frontiers in Cellular and Infection Microbiology, 2025)
Mycoplasma pneumoniae is one of the most significant pathogens responsible for respiratory infections in humans. Macrolides are recommended as the first-line treatment for M. pneumoniae infection. The prevalence of macrolide-resistant M. pneumoniae has increased significantly in recent decades, particularly in China. The mechanisms of resistance in M. pneumoniae to macrolides have been extensively studied in pediatric patients. However, a paucity reports regarding the resistance characteristics and mechanisms exhibited in adults. The aim of this study was to elucidate the resistance of M. pneumoniae to macrolides and the underlying mechanisms in adult patients. Pharyngeal swab specimens were collected from adult patients presenting with subacute cough or community-acquired pneumonia at our hospital from January 2011 to June 2017 to identify and isolate M. pneumoniae strains. The antimicrobial susceptibility of these isolates to 3 macrolide antibiotics was assessed using broth microdilution method. The 23S rRNA genes of macrolide-resistant M. pneumoniae strains were sequenced, and the presence of target methylation genes (ermA, ermB, and ermC), efflux pump genes (mefA, mefA/E, msrA, and msrA/B), and the macrolide resistance gene mphC was identified through polymerase chain reaction (PCR) testing. Additionally, MICs were determined with and without the efflux pump inhibitor reserpine. A total of 72 M. pneumoniae strains were isolated from adult patients, with 41.7% (30/72) exhibiting macrolide resistance. Among the 3 macrolides tested, the 16-membered-ring midecamycin exhibited the greatest activity (MIC90: 16 µg/ml) against M. pneumoniae. All macrolide-resistant M. pneumoniae strains harbored mutations at the 2063 site in domain V of the 23S rRNA gene. Two macrolide-resistant M. pneumoniae clinical isolates were found to harbor the efflux pump genes msrA/B and mefA. The efflux pump inhibitor reserpine reduced the MIC for azithromycin in these two strains to a quarter of their original values. In summary, macrolide-resistant M. pneumoniae is commonly observed among adults in Beijing. Point mutations are the primary mechanism responsible for macrolide resistance in adults with M. pneumoniae. Additionally, the efflux pump mechanism may contribute partially to this resistance. Midecamycin presents a promising alternative drug for treating M. pneumoniae infections, particularly in cases of azithromycin-resistant M. pneumoniae infection in young children.